Health-related quality of life and mental well-being of healthy and diseased persons in 8 countries: Does stringency of government response against early COVID-19 matter?. (September 2021) - Long, Di; Haagsma, Juanita A.; Janssen, Mathieu F.; Yfantopoulos, John N.; Lubetkin, Erica I.; Bonsel, Gouke J.
Abstract: Objectives: Our study aimed to (1) assess health-related quality of life (HRQoL) and mental well-being of healthy and diseased persons in the general population during the early stage of the COVID-19 pandemic and (2) examine the relationship between HRQoL and mental well-being and individual characteristics and government response against COVID-19, as measured by the stringency index. Methods: A web-based survey was administered to a cohort of persons from the general population of eight countries: Greece, Italy, the Netherlands, Russia, South Africa, Sweden, the United Kingdom (UK) and the United States of America (US) from April 22 to May 5 and May 26 to June 1, 2020. Country-level stringency indices were adopted from the COVID-19 Government Response Tracker. Primary outcomes were HRQoL, measured using the EQ-5D-5L, and mental well-being, measured using the World Health Organization-5 Well-Being (WHO-5). Findings: 21, 354 respondents were included in the study. Diseased respondents had lower EQ-5D-5L and WHO-5 scores compared to healthy respondents. Younger respondents had lower WHO-5 scores than older respondents. The stringency index had a stronger association with the EQ-5D-5L and WHO-5 among diseased respondents compared to healthy respondents. Increasing stringency was associated with an increase in EQ-5D-5L scores but a decrease in the WHO-5 index. Conclusion: The stringency of government response is inversely related to HRQoL and mental well-being with a small positive relation with HRQoL and strong negative relation with mental well-being. The magnitude of effects differed for healthy and diseased persons and by age but was most favourable for diseased and older persons. Highlights: Persons with chronic conditions scored lower on EQ-5D-5L and WHO-5 domains, resulting in worse HRQoL and mental well-being. An age gradient was found where younger persons had worse mental well-being than older persons. Stringency of government response had opposite patterns for HRQoL and mental well-being. The magnitude of effects of stringency differed for healthy and diseased persons but was most favourable for diseased persons. Not feeling protected against COVID-19 had the one of the most negative association with mental well-being